Extraction by enzymatic hydrolysis and analysis of dyes natural from stover quinoa (Chenopodium quinoa) for application in the food industry - Fernando Antero Torres Vela (2017)
Pectinases and cellulase were isolated from Trichoderma sp. and Aspergillus niger for the extraction of dyes (betalains) as an alternative for chemical methods, using as culture medium the stubble of quinoa, CMC 0.5% and pectin 0.75% were used as sources of carbón. For getting a dye in a natural way. The evaluation of the enzymatic activities, gives values of 18.13 mg of glucose/ml for the celulolitic extract and a value of 3.70 mg sugar reducer/ml for the pectinolitic extract; with these enzymes the dyes were extracted, having high yields in colors red, violet, orange, and yellow with 22% and 24% respectively, the lowest yield were obtained from the stems and branches giving 11.67%.The betalains were determinated through different tests and an evaluation the antioxidant activity was made. Also a cost analysis was prepared by obtaining a value of US$ 0.55 per gram. Beck fabric and food products testing, determined that they are related to animal fibers (sheep’s wool), and in foods such as milk and yogurt, had better affinity because the thermolabile thereof. Finally a juice was made with natural dye of quinoa.